(untitled) (Journal of Nepal Geological Society, 2001)
A normal fault named as the Danuwargaun Fault was discovered in the southern margin of the Kathmandu Valley. The fault is trending NE-SW and dipping 80 to 90°at NW. The secondary minor faults run along the fault, and a sand dyke intrudes into flu vial beds, trending N 54°E with dip of 80° toward NW. As the northeastern extension of the fault seems to cut the Lukundol Formation and terrace gravel of the Chapagaun Formation (Shrestha et al. 1998), the fault might be active. A change of flow direction of the Bagmati River from N-S to NE-SW near the fault exposure suggests that the draining of the Palaeo-Kathmandu Lake was possibly caused by faulting in the southern margin of the valley.